A stepping gait trajectory design based on hip height variation of swing leg for the balance of lower extremity exoskeleton. Issue 2 (26th November 2019) - Yang, Canjun; Wang, Hansong; Zhu, Qihang; Liu, Xiangzhi; Yang, Wei; Ma, Zhangyi; Wei, Qianxiao
Abstract : Purpose: Lower extremity exoskeletons have drawn much attention recently due to their potential ability to help the stroke and spinal cord injury patients to regain the ability of walking. However, the balance of the human-exoskeleton system (HES) remains a big challenge. Usually, patients use crutches to keep balance when they wear exoskeleton. However, the balance depends greatly on the patient's balance ability and will be inevitably poor occasionally, which often causes the landing in advance of HES. The purpose of this paper is to propose a real-time stepping gait trajectory planning method based on the hip height variation of the swing leg to solve the problem. Design/methodology/approach: The hip height of the swing leg was analyzed and measured. The simulation with MATLAB and the experimental test with the prototype of the proposed gait were conducted to verify its feasibility. Findings: With the proposed method, HES can achieve successful step even when the balance kept by crutches is poor. Research limitations/implications: Instead of actively avoiding the poor balance due to the instability caused by gravity, the method just modifies the stepping gait passively to avoid the landing in advance when the poor balance appears. In addition, it may not work well when the balance is too poor. Moreover, the proposed gait is just used in the initial stage of rehabilitation training. Besides, the step length of the gait must be limited for comfort. Originality/value: A real-time stepping gait trajectory planning method based on the hip height variation of the swing leg is first proposed and its feasibility to avoid the landing in advance when the balance kept by the crutches is poor has been preliminary verified.